1981
DOI: 10.1346/ccmn.1981.0290306
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Some Large Organic Cations with Bentonite in Dilute Aqueous Systems

Abstract: Abstract--Adsorption studies indicate that paraquat, diquat, and thionine are bound on bentonite by amounts greater than the measured cation-exchange capacity (CEC) of the clay. Methylene blue, new methylene blue, and malachite green are bound by amounts equal to the CEC. The unipositive organocations form aggregates on the clay surface. Aggregation increases with ionic strength and increases the apparent adsorption capacity by 25%. The aggregates are removed by washing with distilled water. Desorption studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
2

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 18 publications
4
35
0
2
Order By: Relevance
“…46 In the present study, ionic strength of the solution exhibited some effect on adsorption of montmorillonite. The amount of MB adsorbed onto montmorillonite was decreased with increasing concentration of NaCl in solution ( Figure 6).…”
Section: 45mentioning
confidence: 51%
“…46 In the present study, ionic strength of the solution exhibited some effect on adsorption of montmorillonite. The amount of MB adsorbed onto montmorillonite was decreased with increasing concentration of NaCl in solution ( Figure 6).…”
Section: 45mentioning
confidence: 51%
“…The extended model is applied to the adsorption of two monovalent cationic organic dyes to the surface of montmorillonite, namely methylene blue (MB) (Pham Thi Hang and Brindley, 1970;Narine and Guy, 1981) and thioflavin T (TFT), which has been found to be effective in photostabilizing an insecticidal nitromethylene heterocycle on the surface of montmorillonite . The relative strengths of interactions between these organic cations and the clay are also compared with those of sodium and cesium.…”
Section: Copyright 9 1988 the Clay Minerals Societymentioning
confidence: 99%
“…Several studies have focused on the adsorption of cationic organic dyes to negatively charged smectites (Chu and Johnson, 1979;De et al, 1974;Ghosal and Mukherjee, 1972;Grauer et al, 1984;Pham Thi Hang and Brindley, 1970;Narine and Guy, 1981;Venugopal and Nair, 1974), Margulies et al (1985 suggested a method of photostabilization of pesticides which is based on coadsorbing on a clay surface the photolabile pesticide and an adequate organic cation that acts as energy acceptor. In such a system the organic cation must be strongly attached to the surface of the clay in order to prevent contamination of soil and water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has not been shown that the binding affinities to montmorillonite of other inorganic cations such as NH4 + or Ba 2+ are extremely large. On the other hand, organic cations have been found to adsorb strongly to clays (Chu and Johnson, 1979;De et al, 1974;Ghosal and Mukherjee, 1972;Grauer et al, 1984;Lagaly, 1984;Mortland, 1970;Narine and Guy, 1981;Raussel-Colom and Serratosa, 1987;Theng, 1974;Venugopal and Nair, 1974). The organic cations methylene blue (MB) and thioflavin T (TFT) were previously shown to have binding coefficients of at least l0 s and 109 M -1 (Margulies et al, 1988).…”
Section: Introductionmentioning
confidence: 99%